2019
DOI: 10.1038/s41598-019-44162-x
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Mineral Carbonation of Electric Arc Furnace Slag Under Microwave Irradiation

Abstract: The indirect mineral carbonation of industrial residues is one of the potential technologies for CO 2 sequestration. In this paper, the leaching and carbonation of electric arc furnace (EAF) slag under microwave irradiation was investigated. The experimental results show that the main reactive calcium-containing phase in the EAF slag carbonation process is calcium silicate, and the final leaching ratio of larger particles is lower than that of smaller particles due to the silica layer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…First, the process was more straightforward and required no additives. Traditional vaterite synthesis often involves crystal modifiers such as organic compounds (e.g., ethanol, sucrose, amino acids) or high-energy processes (e.g., ultrasound, microwave) to reduce the crystal surface energy. In contrast, our approach simplified the vaterite formation control through precise pH adjustment (pH ∼ 10.6), maintaining an NH 4 + /Ca 2+ ratio close to 5 and taking into consideration leached metal ions. Second, our process demonstrated a high utilization efficiency of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…First, the process was more straightforward and required no additives. Traditional vaterite synthesis often involves crystal modifiers such as organic compounds (e.g., ethanol, sucrose, amino acids) or high-energy processes (e.g., ultrasound, microwave) to reduce the crystal surface energy. In contrast, our approach simplified the vaterite formation control through precise pH adjustment (pH ∼ 10.6), maintaining an NH 4 + /Ca 2+ ratio close to 5 and taking into consideration leached metal ions. Second, our process demonstrated a high utilization efficiency of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As the most of the calcium in the desulfurization slag exists in the form of calcium oxide and silicate, calcium can be leaching by ammonium chloride solution with high selectivity [14,15] , and it will reduce the addition of texturizine agent effectively. In addition, our preliminary experiments [16,17] also showed that the filtrate of slag leaching by NH4Cl is a high purity system of CaCl2-NH4Cl-NH3-H2O, and high purity and commercial calcium carbonate can be prepared by blowing carbon dioxide gas. The carbonization process was spontaneous, and ammonium chloride could be recycled during the leachingcarbonization process.…”
Section: Introductionmentioning
confidence: 88%
“…In terms of particle size, Owais et al [30] investigated three distinct particle sizes ranging between 0.50 µm, 50-74 µm, and 74-125 µm and determined the optimum particle size of 0-50 µm with greater elution efficiency. Similarly, numerous investigations have found that smaller particle size leads to a higher elution efficiency [31,32]. Previous studies indicated that elution efficiency is directly proportional to extractant concentration and temperature.…”
Section: Introductionmentioning
confidence: 94%